2019
DOI: 10.31219/osf.io/qkd57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Intellectualism, Populism, and Motivated Resistance to Expert Consensus

Abstract: Scholars have maintained that public attitudes often diverge from expert consensus due to ideology-driven motivated reasoning. However, this is not a sufficient explanation on less salient and politically-charged questions. I argue that more attention needs to be given to anti-intellectualism – the generalized mistrust of intellectuals and experts. I make three main contributions using the General Social Survey and a survey of 3,600 Americans on Amazon Mechanical Turk. First, I provide evidence of a strong ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 11 publications
3
71
0
3
Order By: Relevance
“…With this secondary analysis we aimed to explore public awareness and perceptions of the 'replication crisis' utilizing an existing nationally representative survey data set. What motivated us to investigate specifically whether AfD support predicts awareness and perceptions was previous theoretical and empirical research suggesting that criticisms of science often interact or coincide with populist ideas (e.g.,Huber, 2020;Krämer and Klingler, 2020;Mede and Schäfer, 2020;Merkley, 2020).…”
mentioning
confidence: 99%
“…With this secondary analysis we aimed to explore public awareness and perceptions of the 'replication crisis' utilizing an existing nationally representative survey data set. What motivated us to investigate specifically whether AfD support predicts awareness and perceptions was previous theoretical and empirical research suggesting that criticisms of science often interact or coincide with populist ideas (e.g.,Huber, 2020;Krämer and Klingler, 2020;Mede and Schäfer, 2020;Merkley, 2020).…”
mentioning
confidence: 99%
“…For example, a 2019 survey of Americans found that 43% agreed that research scientists "feel superior to others" (Pew Research Center 2019). This finding echoes long-standing anti-intellectual currents in American public opinion (Cramer 2016;Gauchat 2012;Merkley 2020;Motta 2018;Zhang and Mildenberger 2020). 1 For instance, Hofstadter (1966, 273, 275) noted that "applied science would have been immensely useful to farmers" in the nineteenth century, yet there was great "resentment" toward interacting with those who advocated using scientific methods to improve farming.…”
mentioning
confidence: 62%
“…Lower education is also associated with affinity for such movements (Gidron and Hall, 2017; Spruyt, Keppens, and Van Droogenbroeck, 2016). Indeed, leaders often use anti‐intellectualism as a tool, clumping elites and the educated together and encouraging a rejection of the “experts” and a reliance on one's “gut and leader” (Merkley, 2020). Jaffe (2020) notes that there are racial, linguistic, citizenship, sexual, and regional cleavages within class groupings, but income and education remain important factors in the shift toward RWP parties and movements.…”
Section: Thin Right‐wing Populism and Its Supportersmentioning
confidence: 99%